Heritage Site Visits: Impact on National Identity Formation in High School Students - Weni Andiko (Inspire Global Insight Journal, 2026)
Purpose of the study: This experimental study investigated the effect of structured heritage site visits on national identity formation among high school students in Pekanbaru City, Indonesia, examining changes in national pride, cultural knowledge, and civic engagement attitudes. Materials and methods: A randomized controlled trial was conducted with 240 high school students (aged 15-17 years) from six schools in Pekanbaru City. Participants were randomly assigned to experimental (n=120) or control (n=120) groups. The experimental group participated in guided visits to three significant Indonesian heritage sites over eight weeks, while the control group continued regular classroom activities. National identity was measured using the National Identity Scale (NIS), Cultural Knowledge Assessment (CKA), and Civic Engagement Questionnaire (CEQ) administered pre- and post-intervention. Results: Significant improvements were observed in the experimental group compared to controls across all measures. National Identity Scale scores increased by 23.4% (p<0.001), Cultural Knowledge Assessment scores improved by 31.2% (p<0.001), and Civic Engagement Questionnaire scores rose by 18.7% (p<0.01). Effect sizes were large for national identity (Cohen's d = 1.24) and cultural knowledge (Cohen's d = 1.67), and moderate for civic engagement (Cohen's d = 0.73). Conclusions: Structured heritage site visits significantly enhance national identity formation among high school students. These findings suggest that experiential learning through heritage tourism can serve as an effective educational intervention for fostering national consciousness and cultural appreciation in adolescents.